The academic industry's response to generative artificial intelligence - Nir Kshetri (International Telecommunications Society (ITS), 2024)
This paper aims to highlight how disruptive changes such as generative artificial intelligence (GAI) have led to confusion in the academic industry and created an environment of uncertainty for academic entities. Drawing on institutional theory, it examines the discursive legitimacy and responses of key actors in academia to the introduction of GAI tools, shedding light on the complex dynamics shaping the future of education in the age of GAI. The paper provides details of changing response of the academic industry to GAI as a result of academic institutions' evaluation of value creation potential of GAI, their engagement in isomorphic actions to control and gain resources from key actors, and institutional change agents' actions. It attempts to explain the roles of diverse categories of institutional change agents in creating new institutions around GAI. We discuss how these agents theorize such changes and facilitate the diffusion of new ideas related to GAI.
Keywords: 330; Academic industry; institutional change agent; plagiarism; superstitious learning; theorization; uncertainty